Bankruptcy Regulation and Self-Employment Entry: The Moderating Roles of Income Share, Parenthood, and Hybrid Entrepreneurship. (November 2021) - Schulz, Matthias; Schwens, Christian; Fisch, Christian
We investigate how individual factors moderate the impact of bankruptcy exemption levels—that is, the amount of wealth individuals can keep in case of bankruptcy—on entry into self-employment. Conceptually, we combine Prospect Theory's axiom of diminishing sensitivity with insights from research on entrepreneurial failure. We hypothesize that individuals who face higher financial, social, or psychological costs because of bankruptcy will be less sensitive to higher exemption levels than will those who face lower costs across these dimensions. Our empirical results, which are based on a quasi-natural experiment in the United States, support our theoretical predictions.